2006
DOI: 10.1096/fj.06-6503fje
|View full text |Cite
|
Sign up to set email alerts
|

Na,K‐ATPase α1‐subunit dephosphorylation by protein phosphatase 2A is necessary for its recruitment to the plasma membrane

Abstract: In alveolar epithelial cells, G-protein coupled-receptors agonists (GPCR) induce the recruitment of the Na,K-ATPase to the plasma membrane. Here we report that for the recruitment of the Na,K-ATPase to occur, dephosphorylation of its alpha1-subunit at serine 18 is necessary, as demonstrated by in vitro phosphorylation, mutation of the serine 18 to alanine, and use of a specific phospho-antibody. Several approaches strongly suggest dephosphorylation to be mediated by protein phosphatase 2A (PP2A): 1) Na,K-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
(79 reference statements)
0
44
0
Order By: Relevance
“…Human lung cancer A549 cells show many characteristics of ATII cells (Lieber et al, 1976), including the regulation of the Na,K-ATPase Lecuona et al, 2006) but do not form tight epithelial monolayers, whereas canine renal epithelial MDCK cells and human gastric epithelial HGE-20 cells form tight junctions. Western blot analysis using two different antibodies against human FXYD5 detected a major band at ∼32 kDa in A549, human ATII (hATII), MDCK and HGE-20 cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human lung cancer A549 cells show many characteristics of ATII cells (Lieber et al, 1976), including the regulation of the Na,K-ATPase Lecuona et al, 2006) but do not form tight epithelial monolayers, whereas canine renal epithelial MDCK cells and human gastric epithelial HGE-20 cells form tight junctions. Western blot analysis using two different antibodies against human FXYD5 detected a major band at ∼32 kDa in A549, human ATII (hATII), MDCK and HGE-20 cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A549 cells are from a human alveolar epithelial cell line that shows many characteristics of ATII cells (Lieber et al, 1976), including the regulation of the Na + /K + -ATPase, and are more easily transfected than primary ATII cells Dada et al, 2003;Lecuona et al, 2006). AS160 phosphorylation was assessed with a phospho-Akt substrate (pAS) antibody after immunoprecipitation with a FLAG antibody.…”
Section: -Atpase Translocationmentioning
confidence: 99%
“…A549 cells expressing V5-tagged rat Na + /K + -ATPase  1 subunit were generated as described previously (Lecuona et al, 2006) and grown in DMEM with the addition of 3 M ouabain to suppress the endogenous human Na + /K + -ATPase  1 subunit. Stably transfected GFP-Rab10 A549 cells were generated by transfecting the cells with GFP-WT-Rab10; selection was performed with media containing 1 g/ml puromycin.…”
Section: Isolated Perfused Rat Lung Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in AECs of normal rats, the stimulation of DA receptors increases lung edema clearance by increasing NKA function. Specific studies have shown that DA promotes protein phosphatase 2A translocation to the membrane fraction, leading to dephosphorylation of the NKAα 1 subunit at the Ser-18 residue and its recruitment to the cell plasma membrane of alveolar epithelial type II (ATII) cells via DA receptors, which results in increased NKA activity (51,52) and lung fluid clearance (53). Moreover, new evidence has revealed that administration of a tyrosine-enriched diet to rats increases endogenous DA production, which causes increased NKA protein abundance in AECs, leading to increased NKA activity via the activation of D 1 receptors (54).…”
Section: Da Receptor-mediated Regulation Of Nkamentioning
confidence: 99%